Clinical researchMaternal smoking and ethnic origin, association with birth weight and NICU admission - Donaldson, Nora; Rao, Harish; Hannam, Simon; Rafferty, Gerrard F.; Greenough, Anne (Archives of Medical Science, 2008)
Introduction: Despite anti-smoking campaigns, smoking in pregnancy is common and has adverse consequences for the infant. Maternal smoking may vary according to ethnic origin. Our aims were to determine if indeed maternal smoking habits varied according to ethnicity, and whether adverse effects of maternal antenatal smoking on infants, as indicated by reduced birthweight and need for NICU admission, varied according to ethnic origin. Material and methods: A maternal and infant database was interrogated. Midwives asked mothers about their ethnic origin and smoking habits and entered data prospectively. The number of cigarettes smoked used in the analysis was the minimum number the mothers admitted to smoking; heavy smokers were those smoking more than five cigarettes per day. Data were analysed from 3595 women. The majority were either Caucasian (39%), Asian (5%), Caribbean (17%) or African (36%). Seven hundred and forty of the women were smokers. Results: A greater proportion of Caucasian (34%) and Caribbean (28%) women admitted to smoking compared to Asian (7%) and African (5%) women (P<0.001). Heavy smoking was most common amongst Caucasian women (P<0.001). Maternal ethnicity (P<0.001) and smoking (P<0.001) significantly influenced birth weight. Among women who smoked between 5 and 10 cigarettes per day, there was a dose-dependent adverse effect on birth weight. Multivariate analysis demonstrated that significant associations of NICU admission were gestational age, birth weight and parity of the mother, but not maternal ethnicity or smoking. Conclusions: Heavy smoking is associated with a dose-dependent adverse effect on birth weight and is most common in Caucasian women.